Evidence-based gender equality policy and pay in Latin America and the Caribbean: Progress and challenges - Rosangela Bando Grana (Latin American Economic Review, 2019)
This paper aims to identify the main contributing factors to the observed gender pay inequality in the last 10 years in Latin America and the Caribbean. It also aims to identify the main restrictions to design evidence-based policy. The average woman in the region works 25 h more per month than the average man. Yet only half of women in the region are paid for or otherwise profit from their work. Work without formal pay leads to weak protection of human rights and limits civic participation. Moreover, gender inequality deters economic development and fosters income inequality. Research shows gender gaps result from the interactions of social norms and biological differences. The challenges to generating effective policies include the difficulty of identifying relevant mechanisms to explain gaps, the cost of collecting and analyzing relevant data, and the complexity associated with determining pertinent features of gender gaps. Collection and analysis of those mechanisms, data, and features are critical to learning how to correct gender gaps going forward.
Keywords: J10; J16; J70; O54; 330; Gender inequality; Gender gaps; Latin America and the Caribbean